Regions of incompatibility in single-stranded DNA bacteriophages phi X174 and G4. - van der Avoort, H G (1984)
The intracellular presence of a recombinant plasmid containing the intercistronic region between the genes H and A of bacteriophage phi X174 strongly inhibits the conversion of infecting single-stranded phi X DNA to parental replicative-form DNA. Also, transfection with single-stranded or double-stranded phi X174 DNA of spheroplasts from a strain containing such a "reduction" plasmid shows a strong decrease in phage yield. This phenomenon, the phi X reduction effect, was studied in more detail by using the phi X174 packaging system, by which plasmid DNA strands that contain the phi X(+) origin of replication were packaged as single-stranded DNA into phi X phage coats. These "plasmid particles" can transduce phi X-sensitive host cells to the antibiotic resistance coded for by the vector part of the plasmid. The phi X reduction sequence in the resident plasmid strongly affected the efficiency of the transduction process, but only when the transducing plasmid depended on primosome-mediated initiation of DNA synthesis for its conversion to double-stranded DNA. The combination of these results led to a model for the reduction effect in which the phi X reduction sequence interacted with an intracellular component that was present in limiting amounts and that specified the site at which phi X174 replicative-form DNA replication takes place. The phi X reduction sequence functioned as a viral incompatibility element in a way similar to the membrane attachment site model for plasmid incompatibility. In the DNA of bacteriophage G4, a sequence with a similar biological effect on infecting phages was identified. This reduction sequence not only inhibited phage G4 propagation, but also phi X174 infection.